PENGARUH KONSERVATISME AKUNTANSI, UKURAN PERUSAHAAN TERHADAI EARNING RESPONSE COEFFICIENT (ERC) PADA PERUSAHAAN SEKTOR TEKNOLOGI - Nurlaelah, Nurlaelah; Hanifah, Hanifah; Muslimah, Shifa Ul (The Asia Pacific Journal Of Management Studies, 2023)
The purpose of this study was to determine the effect of accounting conservatism, company size on earnings response coefficient (ERC) in technology companies listed on the Indonesia stock exchange for the 2019-2021 period. The purpose of this research is to provide references and knowledge about whether or not there is an influence given by accounting conservatism and company size on the earning response coefficient to technology companies listed on the BEI. The research method used is a quantitative method. Quantitative writing method is used to analyze the relationship between one variable and another or how one variable affects other variables. The t-count value of accounting conservatism (X1) is -0.138, smaller than the t-table of 2.0195. (-0.138 < 2.0195). From the above test, the significance of accounting conservatism (X1) is 0.725, which is greater than 0.05, which means that accounting conservatism has no effect on Earning response coefficient (ERC). The t-count value of company size (X2) is 0.390 which is smaller than the t-table of 2.0195. (0.390 < 2.0195). From the above test, the significance of firm size (X2) is 0.390, which is greater than 0.05, which means that firm size has no significant effect on Earning response coefficient (ERC). The results of the study indicate that accounting conservatism and firm size have no significant effect on the Earning Response Coefficient (ERC).